Micropolíticas da juventude e visibilidades transversais: in(ter)venções audiovisuais na Restinga, em Porto Alegre - Gorczevski, Deisimer (Universidade do Vale do Rio do Sinos, 2007)
In the city of Porto Alegre, more specifically at Restinga, a neighborhood with forty years of history and resistance to social and media visibility due to confinement, a minority segment – the young, producers and managers of “mixed state” media, especially community audiovisuals – is examined, with their ways of creating alliances and groups of periphery communication. These groups, among other actions, participate, propose and carry out audiovisual workshops. This work analyzes the life history of the young at Restinga, their in(ter)ventions and audiovisual production in terms of their relationship with mediators and events that invest in the desire for “other visibilities,” from theatrical experimentation, the propositions of the Culture Decentralization Project (culture committee, video and cinema workshops, among others), the creation and action of the community radio station, the implementation of a Multimedia Studio, the creation of the Restinga and Extremo Sul Education Forum, the Cineesquemanovo F
Keywords: micropolítica; periferia urbana; Porto Alegre; produção audio visual; Restinga; comunicação comunitária; jovens; audiovisual productions; periphery; youth; micropolitics; Ciências Sociais Aplicadas